KEBERLAKUAN HUKUMAN CAMBUK DALAM QANUN JINAYAT DITINJAU DARI PERSPEKTIF HAK ASASI MANUSIA - Pajaru Lombu (JURNAL TRANSFORMATIF UNKRISWINA SUMBA, 2019)
This research is about criticizing the practice of Qanun Jinayat, which is a criminal law unit, which applies to the Acehnese people formed based on the values of Islamic law. The purpose of the whipping penalty is to correct the perpetrators by making them deterrent. The whipping punishment violates human rights as stated in Article 28G paragraph (2) of the Constitution of 1945. Human rights are the basic laws or the highest legal norms to be obeyed by the state. The fact of human rights is to safeguard the full security of human existence that protects human dignity and serves to control legal rights.